Proofs of Prophecy and the Refutation of the Isma'iliyya : the Kitab Ithbat nubuwwat al-nabi by the Zaydi al-Mu'ayyad bi-Ilah al-Haruni (d. 411/1020). - Lika, Eva-Maria (Welten des Islams - Worlds of Islam - Mondes de l'Islam., 2017)
Al-Mu'ayyad bi-llah al-Haruni (d. 411/1020) was a representative of the intellectual center of the Zaydiyya in Northern Iran and a student of the leading Muʻtazilite theologians of the time. In his Kitab Ithbat nubuwwat al-nabi he presents a proof of prophecy of Muḥammad and a refutation of the Isma'ilyya.The present volume explores the historical and intellectual context of the oeuvre and includes a partial critical edition of the text.